The Phenomenon of Political Dynasty in Regional Head Elections in Indonesia - Rannie, Mahesa; Saraswati, Retno; Wisnaeni, Fifiana (Nurani, 2023)
Direct regional head elections (Pilkada) provide opportunities for civilian circles to become candidates for regional heads, but this has created a new problem, namely the rampant phenomenon of dynasty politics. This condition is quite concerning, not only because incumbent families participate in the replacement, but also due to the negative effects of the desire for power. Therefore, it is necessary to analyze why the phenomenon of dynasty politics emerges and its influence on the implementation of Pilkada. Additionally, it is important to analyze how this phenomenon is viewed from the perspectives of human rights, law, and justice. This is in line with the research objective, which is to analyze the causes of the emergence of dynasty politics and its influence on Pilkada, as well as to analyze the phenomenon from various perspectives. The research method used is socio-legal. The conclusion drawn is that the emergence of dynasty politics is due to the recruitment function of political parties not being based on quality and the weakness of regulations. This has consequences for the implementation of Pilkada, resulting in candidates who are of lower quality and competence. From a human rights perspective, the regulations regarding dynasty politics may indeed violate human rights, but considering the widespread phenomenon of dynasty politics, it is not excessive to establish rules similar to those previously included in Law Number 8 of 2015. From a legal perspective, election laws and political parties should also be improved. All of these efforts are intended to prevent the further spread of dynasty politics, as it can result in injustice for other individuals who wish to run for office.